Investigation of Invariant Sets of Itô Stochastic Systems with the Use of Lyapunov Functions - Stanzhitskii, A. N. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
By using Lyapunov functions, we obtain conditions for the invariance and stochastic stability of invariant sets of Itô-type systems.